PROFILE OF TEACHER CAREER SATISFACTION: A CULTURAL REVIEW ON SCHOOL QUALITY - Arumsari, Cucu; Suherman, Uman; Nurihsan, Juntika; Yustiana, Yusi Riksa; Budiamin, Amin; Yulianto, Eko (Universitas Pendidikan Indonesia, 2024)
This study used a quantitative survey approach to analyze the career satisfaction of vocational schoolteachers in the City of Tasikmalaya who members of the Guidance and Counseling Teacher Deliberations (MGBK) are. A total of 40 respondents, with 31 women (77.5%) and 9 men (22.5%). The research instrument used the Career Satisfaction Scale (CSS) with adequate internal reliability. The results of the study show that women have the same opportunities in careers as vocational teachers, even though in the teaching profession women are more dominant. Factors such as gender stereotypes and disparities in access to mentors and professional networks can influence women's career satisfaction. In terms of age, respondents ranged in age from 22 to 50 years, with variations in frequency for each age group. Previous research has shown that stereotypes about reduced performance and career satisfaction in older workers are not entirely accurate. Older workers can have equal or even higher levels of career satisfaction than younger workers. In terms of education, most of the respondents (62.5%) had a bachelor's degree, while the rest (37.5%) had a master's degree. Previous studies have shown that the compatibility of education with work is positively related to career satisfaction. Most respondents (65%) experienced moderate levels of career satisfaction, followed by a small number who experienced high (17.5%) and low (17.5%) levels of career satisfaction. Factors such as a sense of accomplishment, success on the job, good relationships with colleagues and superiors, recognition received, and alignment with interests and values can influence career satisfaction. Interviews with counseling teachers showed that high school quality has a positive impact on career satisfaction. A conducive work environment, principal support, adequate resources, and a positive learning climate create a satisfying work experience for counseling teachers. Overall, this study provides insight into the career satisfaction of vocational schoolteachers in Tasikmalaya City and the factors that influence it. This study can be the basis for the development of policies and programs aimed at increasing the career satisfaction of vocational teachers